THEORY ON THE EXPERIMENTAL DATA FOR THE MOMENTUM PROTON DISTIBUTIONS IN CHANNEL - Afanas’eva, N.V.; Burkova, N.A.; Zhaksybekova К.А.; Safiulin, D.R. (Recent Contributions to Physics, 2009)
Within the -model for the ground state of nuclei and first excited one 2+, 1 the proton momentum distributions have been calculated in fragmentation channel. A comparison with available theoretic calculations as well experimental data on the processis given.